Developing a guideline for clinical trial protocol content: Delphi consensus survey - Tetzlaff, Jennifer M; Moher, David; Chan, An-Wen (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Recent evidence has highlighted deficiencies in clinical trial protocols, having implications for many groups. Existing guidelines for randomized clinical trial (RCT) protocol content vary substantially and most do not describe systematic methodology for their development. As one of three prespecified steps for the systematic development of a guideline for trial protocol content, the objective of this study was to conduct a three-round Delphi consensus survey to develop and refine minimum content for RCT protocols. Methods Panellists were identified using a multistep iterative approach, met prespecified minimum criteria and represented key stakeholders who develop or use clinical trial protocols. They were asked to rate concepts for importance in a minimum set of items for RCT protocols. The main outcome measures were degree of importance (scale of 1 to 10; higher scores indicating higher importance) and level of consensus for items. Results were presented as medians, interquartile ranges, counts and percentages. Results Ninety-six expert panellists participated in the Delphi consensus survey including trial investigators, methodologists, research ethics board members, funders, industry, regulators and journal editors. Response rates were between 88 and 93% per round. Overall, panellists rated 63 of 88 concepts of high importance (of which 50 had a 25th percentile rating of 8 or greater), 13 of moderate importance (median 6 or 7) and 12 of low importance (median less than or equal to 5) for minimum trial protocol content. General and item-specific comments and subgroup results provided valuable insight for further discussions. Conclusions This Delphi process achieved consensus from a large panel of experts from diverse stakeholder groups on essential content for RCT protocols. It also highlights areas of divergence. These results, complemented by other empirical research and consensus meetings, are helping guide the development of a guideline for protocol content.